EDUCATIONAL AND PRACTICAL CENTER – AN INNOVATIVE EDUCATIONAL HUB FOR TRAINING QUALIFIED WORKERS FOR THE POST-WAR RECONSTRUCTION (Innovative professional education, 2025)
The paper analyzes the role and importance of educational and practical centers for training qualified specialists capable of successfully addressing the main challenges of post-war reconstruction, ensuring the development of strategic sectors of the regional economy, which is the basis for a stable future of the country.
Keywords: vocational (vocational-technical) education, educational and practical centers, modernization of the vocational education system, innovative technologies